Analisis Sistem Informasi AKuntansi Pada Kinerja UMKM DEngan Laporan Keuangan Sebagai Variabel Intervening - Rosita, Rosita; Nugroho, Lailatan; Ilmi, Muhammad Bahrul (Graduasi: Jurnal Bisnis & Ekonomi, 2014)
his study uses object SMEs in order to determine the performance of SMEs byusing the financial statements resulting from Accounting Information Systems (AIS). Design studies are performed using variables of the AIS , financial statements and performance of SMEs . The hypothesis that will be tested are prepared using multiple regression with two steps of testing. The data collection of objects that SMEs in Surakarta. Questionnaires were returned later created tabulation data are then tested the feasibility of the data obtained so as to produce a decent data to be processed in the test data and test hypotheses.Multiple regression of equation I, is to determine the influence of these factors on the financial statements AIS. Equation II was conducted to determine the influence of factors AIS and financial reports on the performance of SMEs. Results from this study is that the AIS (transaction processing system) does not significantly affect the financial statements and the performance of SMEs in the city of Surakarta. AIS (financial reporting system) significantly affect the financial statements but does not affect the performance of SMEs. AIS (management reporting system) affect the financial statements or performance of SMEs either directly or through financial statements , so that financial statements can be regarded as an intermediate variable (intervening) between AIS (management reporting system) on the performance of SMEs . Influence on the performance management reporting system will be very strong when SMEs through intermediate variable (intervening) the financial statements. The advice given in this study that a large number of SMEs (thousands) in Surakarta should be sampled more research to represent the population of the research object.